American georgics : economy and environment in early American literature - Sweet, Timothy, 1960- (Philadelphia : University of Pennsylvania Press, 2002)
"In classical terms the georgic celebrates the working landscape, cultivated to become fruitful and prosperous, in contrast to the idealized or fanciful landscapes of the pastoral. Arguing that economic considerations must become central to any understanding of the human community's engagement with the natural environment, Timothy Sweet identifies a distinct literary mode he calls the American georgic. Offering a fresh approach to ecocritical and environmentally-oriented literary studies, Sweet traces the history of the American georgic from its origins in late sixteenth-century English literature promoting the colonization of the Americas through the mid-nineteenth century, ending with George Perkins Marsh's Man and Nature (1864), the foundational text in the conservationist movement."--Publisher's description.
Cover; Title; Copyright; Contents; Introduction; 1 Economy and Environment in Sixteenth-Century Promotional Literature; 2 ""God Sells Us All Things for Our Labour"": John Smith's Generall Historie; 3 ""Wonder-Working Providence"" of the Market; 4 ""Admirable Oeconomy"": Robert Beverley's Calculus of Compensation; 5 Ideologies of Farming: Crèvecoeur, Jefferson, Rush, and Brown; 6 Cherokee ""Improvements"" and the Removal Debate; 7 ""Co-Workers with Nature"": Cooper, Thoreau, and Marsh; Notes; Works Cited; Index; Acknowledgments.
Includes bibliographical references (pages 203-214) and index.
JSTOR
Keywords: American literature -- History and criticism; Environmental literature -- History and criticism; Pastoral literature, American -- History and criticism; Didactic literature, American -- History and criticism; Economics and literature -- United States -- History; Agriculture in literature; Economics in literature; Nature in literature; Littérature pastorale américaine -- Histoire et critique; Littérature didactique américaine -- Histoire et critique; Économie politique et littérature -- États-Unis -- Histoire; Agriculture dans la littérature.; Économie politique dans la littérature.; Nature dans la littérature.; LITERARY CRITICISM -- American -- General; Agriculture in literature; American literature; Didactic literature, American; Economics and literature; Economics in literature; Environmental literature; Nature in literature; Pastoral literature, American; United States; Hirtendichtung; Ökologie; Wirtschaft; USA; American History; American Studies; Cultural Studies; Literature; Criticism, interpretation, etc; History